2021
DOI: 10.1002/cae.22463
|View full text |Cite
|
Sign up to set email alerts
|

Using handheld user interface and direct manipulation for architectural modeling in immersive virtual reality: An exploratory study

Abstract: This study comparatively investigates the affordances and constraints of two modeling methods for three‐dimensional modeling in immersive virtual reality (IVR): handheld user interface (HUI) and direct manipulation modeling (DM). The experimental study was conducted with 20 graduate students and two domain experts. Data were collected with screen capture videos of the modeling screen and video recordings of the users' gestures during the modeling session. To triangulate the findings for better reliability, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…They collected data through the screen capture video of the modeling screen and the video recording of user gestures during the modeling session. Through the analysis of qualitative coding method, they believed that DM modeling can be digitally input through a new keyboard [9,10]. In their research, Li et al used real-time computer graphics technology, three-dimensional modeling technology and binocular stereo vision technology to study multivision animated character objects in virtual reality technology, designed binocular stereo vision animation system and 3D graphics algorithm for three-dimensional geometric transformation of computer graphics, and studied image output processes such as basic texture technology and basic lighting model used in fragment processing stage [11].…”
Section: State Of the Artmentioning
confidence: 99%
“…They collected data through the screen capture video of the modeling screen and the video recording of user gestures during the modeling session. Through the analysis of qualitative coding method, they believed that DM modeling can be digitally input through a new keyboard [9,10]. In their research, Li et al used real-time computer graphics technology, three-dimensional modeling technology and binocular stereo vision technology to study multivision animated character objects in virtual reality technology, designed binocular stereo vision animation system and 3D graphics algorithm for three-dimensional geometric transformation of computer graphics, and studied image output processes such as basic texture technology and basic lighting model used in fragment processing stage [11].…”
Section: State Of the Artmentioning
confidence: 99%
“…Hence, the level of realism in any use-case can be determined in accordance with the task to be performed or the subject to be taught. Another finding is that there is a negative relationship between the scale of the relevant virtual object (1:1 scale) and usability or task performance [114,117]. One explanation can be that if the virtual object's scale is too large for the user to see holistically, which is the main element of the relevant task, it may cause disorientation.…”
Section: Discussionmentioning
confidence: 99%
“…In AECO/FM education, there is general agreement on the validity of this characteristic to perform various design and operational tasks that can be implemented in the real environment for various use cases [17,44,60]. Tastan et al [117] showed that 1:1 scale negatively influenced 3D-modeling tasks compared to modeling at smaller scales. Sun et al [114] showed that the 1:1 scale is negatively correlated with learning performance compared with smaller scales.…”
Section: Technological Characteristics (Input Factor)mentioning
confidence: 99%
See 2 more Smart Citations